CDKN2A homozygous deletion is a strong adverse prognosis factor in diffuse malignant IDH-mutant gliomas. Issue 12 (12th July 2019) - Appay, Romain; Dehais, Caroline; Maurage, Claude-Alain; Alentorn, Agusti; Carpentier, Catherine; Colin, Carole; Ducray, François; Escande, Fabienne; Idbaih, Ahmed; Kamoun, Aurélie; Marie, Yannick; Mokhtari, Karima; et al.
Abstract: Background: The 2016 World Health Organization (WHO) classification of central nervous system tumors stratifies isocitrate dehydrogenase ( IDH )–mutant gliomas into 2 major groups depending on the presence or absence of 1p/19q codeletion. However, the grading system remains unchanged and it is now controversial whether it can be still applied to this updated molecular classification. Methods: In a large cohort of 911 high-grade IDH -mutant gliomas from the French national POLA network (including 428 IDH -mutant gliomas without 1p/19q codeletion and 483 anaplastic oligodendrogliomas, IDH -mutant and 1p/19q codeleted), we investigated the prognostic value of the cyclin-dependent kinase inhibitor 2A ( CDKN2A ) gene homozygous deletion as well as WHO grading criteria (mitoses, microvascular proliferation, and necrosis). In addition, we searched for other retinoblastoma pathway gene alterations ( CDK4 amplification and RB1 homozygous deletion) in a subset of patients. CDKN2A homozygous deletion was also searched in an independent series of 40 grade II IDH -mutant gliomas. Results: CDKN2A homozygous deletion was associated with dismal outcome among IDH -mutant gliomas lacking 1p/19q codeletion ( P < 0.0001 for progression-free survival and P = 0.004 for overall survival) as well as among anaplastic oligodendrogliomas, IDH -mutant + 1p/19q codeleted ( P = 0.002 for progression-free survival and P < 0.0001 for overall survival) in univariate and multivariate analysis including age, extent of surgery, adjuvant treatment, microvascular proliferation, and necrosis. In both groups, the presence of microvascular proliferation and/or necrosis remained of prognostic value only in cases lacking CDKN2A homozygous deletion. CDKN2A homozygous deletion was not recorded in grade II gliomas. Conclusions: Our study pointed out the utmost relevance of CDKN2A homozygous deletion as an adverse prognostic factor in the 2 broad categories of IDH -mutant gliomas stratified on 1p/19q codeletion and suggests that the grading of these tumors should be refined.